2013
DOI: 10.1371/journal.pone.0053524
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Characteristics of Low Pathogenic Avian Influenza Virus Isolated from Commercial Poultry in Tunisia

Abstract: ObjectiveEstimate the seroprevalence of influenza A virus in various commercial poultry farms and evaluate specific risk factors as well as analyze their genetic nature using molecular assays.Materials and MethodsThis report summarizes the findings of a national survey realized from October 2010 to May 2011 on 800 flocks in 20 governorates. Serum samples were screened for the presence of specific influenza virus antibodies using cELISA test. Additionally, swab samples were tested by real time and conventional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 34 publications
(39 reference statements)
0
25
1
Order By: Relevance
“…Also, the overall sero prevalence recorded in this study is higher than that (28.7%) reported by Tombari et al (2013) in a study conducted in commercial poultry farms in Tunisia. However, the sero prevalence recorded on LGA bases; Jos North (30%), and Jos South (34%) Nigeria was lower, than that recorded in same study by Tombari et al (2013) in Tunisia where they reported a prevalence of 47.7% in Tunis, 45.7% in Nebeul, and 41.3% for Sfax.…”
Section: Discussioncontrasting
confidence: 86%
“…Also, the overall sero prevalence recorded in this study is higher than that (28.7%) reported by Tombari et al (2013) in a study conducted in commercial poultry farms in Tunisia. However, the sero prevalence recorded on LGA bases; Jos North (30%), and Jos South (34%) Nigeria was lower, than that recorded in same study by Tombari et al (2013) in Tunisia where they reported a prevalence of 47.7% in Tunis, 45.7% in Nebeul, and 41.3% for Sfax.…”
Section: Discussioncontrasting
confidence: 86%
“…Although the H9N2 avian virus subtype is generally not highly pathogenic for avian species, it has been associated with severe morbidity and mortality in poultry following coinfection with other pathogens [11, 12]. Recent findings indicate that the H5N1 viruses responsible for severe human disease contain genetic rearrangements that include several genes from obtained avian H9N2 viruses [13].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of AIV H9N2 infection varies between countries in the Middle East. For example, it was reported to be 40.6% in broilers in Iran (6), 28.7% in different poultry species in Tunisia (20), and 71% in broiler-breeders in Jordan (3).…”
mentioning
confidence: 99%